2020
DOI: 10.1016/j.amepre.2019.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Sexual Assault Health Care Among Homeless Young Adults

Abstract: Introduction: Young adults experiencing homelessness are at increased risk for sexual assault. Receiving a post−sexual assault examination has important implications for HIV and unintended pregnancy prevention; yet, utilization is not well understood. In a population at elevated risk for HIV, unintended pregnancy, and sexual violence, identifying barriers and facilitators to post− sexual assault examination is imperative. Methods: As part of a large, multisite study to assess youth experiencing homelessness ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…This finding is congruent with results rating a lack of service professionals who are trans-positive as the most significant barrier to collaborating across sectors to enhance care. It is also consistent with several previous studies that have identified a lack of training, limited medical knowledge, and scant access to appropriate education among healthcare and social service providers results in inadequate care and experiences of discrimination when trans persons seek supports [13,14,16,[28][29][30]. Organizational representatives indicated that a network could address these problems by supporting providers in becoming more knowledgeable about trans issues and experiences while working to improve their competence to provide trans-affirming care.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This finding is congruent with results rating a lack of service professionals who are trans-positive as the most significant barrier to collaborating across sectors to enhance care. It is also consistent with several previous studies that have identified a lack of training, limited medical knowledge, and scant access to appropriate education among healthcare and social service providers results in inadequate care and experiences of discrimination when trans persons seek supports [13,14,16,[28][29][30]. Organizational representatives indicated that a network could address these problems by supporting providers in becoming more knowledgeable about trans issues and experiences while working to improve their competence to provide trans-affirming care.…”
Section: Discussionsupporting
confidence: 88%
“…Limited access to and availability of appropriate services were identified by representatives of organizations as substantial challenges to the response to trans survivors. As in earlier studies, they associated discrimination and stigma related to being trans and a sexual assault survivor to a lack of trust in accessing healthcare services [13,14,16]. It was mentioned that these experiences intersect with other forms of oppression, including racism and poverty, which further limit access to supports; findings similar to those in research on trans persons experiencing sexual assault and homelessness [37].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The diversity reflected in these organizations shows promise for a network that is able to function in full consideration of the implications of its actions across all types of services, sectors, and geographical regions (Emerson et al, 2012). Additionally, the organizations' diverse nature of supports offered will be critical in addressing the complex needs of trans survivors who may be experiencing multiple intersecting issues (e.g., housing instability, immigration status) that effect their vulnerability to experiencing sexual assault, as well as their interaction with supports postvictimization (James et al, 2016;Kattari & Begun, 2017;Santa Maria et al, 2020).…”
Section: Discussionmentioning
confidence: 99%